Education and training for community pharmacists in mental health practice: how to equip this workforce for the future. Issue 3 (2nd September 2014) - Wheeler, Amanda; Mey, Amary; Kelly, Fiona; Hattingh, Laetitia; K. Davey, Andrew
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the potential approaches to continuing education and training delivery for community pharmacists to equip them to support mental health consumers and carers with illnesses such as depression and anxiety. Design/methodology/approach – Review of national and international literature about community pharmacists' roles, beliefs and attitudes towards mental health, continuing education delivery for the workforce and training recommendations to equip pharmacy workforce. Findings – Training involving consumer educators was effective in reducing stigma and negative attitudes. Interactive and contextually relevant training appeared to be more effective than didactic strategies. Narratives and role-plays (from the perspective of consumers, carers and health professionals) are effective in promoting more positive attitudes and reduce stigma. Flexible on-line delivery methods with video footage of expert and consumer narratives were preferable for a cost-effective programme accessible to a wide community pharmacy workforce. Originality/value – There is a clear need for mental health education for community pharmacists and support staff in Australia. Training should target reducing stigma and negative attitudes, improving knowledge and building confidence and skills to improve pharmacy staff's perceived value of working with mental health consumers. The delivery mode should maximise uptake.